Inflectional and derivational morphological spelling abilities of children with Specific Language Impairment - Critten, Sarah; Connelly, Vincent; Dockrell, Julie E.; Walter, Kirsty (Frontiers in Psychology, 2014)
Children with Specific Language Impairment (SLI) are known to have difficulties with spelling but the factors which underpin these difficulties, are a matter of debate. The present study investigated the impact of oral language and literacy on the bound morpheme spelling abilities of children with SLI. Thirty-three children with SLI (9-10 years) and two control groups, one matched for chronological age (CA) and one for language and spelling age (LA) (aged 6-8 years) were given dictated spelling tasks of 24 words containing inflectional morphemes and 18 words containing derivational morphemes. There were no significant differences between the SLI group and their LA matches in accuracy or error patterns for inflectional morphemes. By contrast when spelling derivational morphemes the SLI group was less accurate and made proportionately more omissions and phonologically implausible errors than both control groups. Spelling accuracy was associated with phonological awareness and reading; reading performance significantly predicted the ability to spell both inflectional and derivational morphemes. The particular difficulties experienced by the children with SLI for derivational morphemes are considered in relation to reading and oral language.